T4 Optically detectable antimicrobial peptides enable the immediate detection of bacteria and fungi in the lung. (12th November 2015) - Akram, AR; Avlonitis, N; Vendrell, M; Chankeshwara, S; McDonald, N; Aslam, T; Scholefield, E; Walsh, T; Haslett, C; Bradley, M; Dhaliwal, K
Abstract : Introduction: The immediate detection of pathogens in the lungs of patients with unexplained pulmonary opacities in the intensive care unit would represent a significant advance in their management. An optical imaging strategy, including the endobronchial administration of bacterial specific Smartprobes, would confer a number of advantages over conventional techniques such as bronchoalveolar lavage, principally real-time detection to immediately inform antimicrobial therapy. The aims of this study were to fluorescently label and iteratively develop anti-microbial peptides to image bacteria in situ in the lung using fibered confocal fluorescence microscopy (FCFM). Methods: Antimicrobial peptides (AMP) have been synthesised on a dendrimeric scaffold (AMP-1) and conjugated to an environmentally sensitive fluorophore called NBD, following the continuous development a linear counterpart. A further construct consists of an AMP with gram-selectivity conjugated to the NBD fluorophore (AMP-2). These are combined with FCFM to allow distal alveolar imaging at micron resolution in an ex vivo ovine model of bacterial infection. Results: AMP-1 demonstrates bacterial binding affinity in a concentration dependent manner and labels a diverse panel of bacteria, including a panel consisting of >70% of ventilator-associated pneumonia causing organisms and the pathogenic fungi Aspergillus fumigatus. AMP-1 demonstrates significantly higher fluorescence over isomolar linear equivalents for E. coli, K. pneumoniae, P. aeruginosa, MSSA, A. baumannii and S. pneumoniae (all p < 0.01), is selective for bacteria over mammalian cells and has improved chemical stability over the linear equivalent when incubated with bronchoaoveolar lavage from patients with acute respiratory distress syndrome. Furthermore, AMP-1 can label E. coli, K. pneumoniae, P. aeruginosa and MSSA in situ in an ex vivo ovine model when instilled endobronchially and imaged with FCFM (pin vitro and remains selective for gram-negative bacteria over mammalian cells. In the ex-vivo model AMP-2 selectively labels the gram-negative bacterial segments ( P. aeruginosa, K. pneumonia and E. coli ) over the gram-positive (MSSA, MRSA and S. pneumoniae ) or control pulmonary segments (all p < 0.05). Conclusions: A Smartprobe/FCFM strategy to immediately detect bacteria with gram selectivity in size relevant pre-clinical models is described, and are undergoing first-in-man translation.